The Relative Merits of Three Methodological Approaches to Studying Women’s Reproductive Health - Gustafson, Diana (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
What methodological approaches might motherhood scholars use to better understandwomen’s experiences of their reproductive health across generations and over time? Traditional quantitative and qualitative longitudinal methodologies have strengthsand limitations as illustrated using examples drawn from the maternal and familialliterature. Data collected across generational cohorts using traditional longitudinalmethods illuminates the complexities of family histories but comes with attendantproblems of participant attrition, dips in team interest and commitment, and theshifting appetite for knowledge. The intergenerational life story approach offers analternative that is less time consuming and less resource intensive. Narrative threadscollected during the Life Story Project illustrate the relative merits of this alternativemethod of inquiry into the ways that women learn about and share reproductivehealth information within families and across generations.